Effects of DHA-Enriched Fish Oil Supplements on Dopamine Receptor Gene Expression in the Cerebral Cortex and Hippocampus Related to the Male Rat’s Weight Gain - Fifi Veronica (Journal of Global Pharma Technology, 2020)
Background: Docosahexaenoic acid (DHA) can penetrate through the barrier between the blood and the brain through simple diffusion and obtains benefits for neurons. Supplementation of DHA-enriched fish oil for seven weeks in young male Wistar rat could alter dopamine (DA) receptor modulation, and it may be related to the increased weight gain. Aim: This present study aims to explore the alteration of the dopamine receptors (D1DR and D2DR) gene expression in the cerebral cortex and hippocampal area, as a top-down circuit control, related to the role of body weight gain as an indicator of food intake. Methods: Twenty samples of Rattus novergicus, aged 7-8 weeks, were randomly grouped into two groups as follows: 10 rats as the control group (CG) and 10 rats in the group that received treatment with fish oil -omega 3 capsules (FOG). CG and FOG were fed with standard laboratory food and received water ad libitum. The treated group (FOG) received 0.2 ml added supplementation of DHA-enrich fish oil (FO) capsules with the daily dose of 30 mg EPA and 45 mg of DHA for 7 weeks via gavage every morning. The body weight of each rat was weighed and recorded every 2 weeks. Results: The weight had increased significantly in the FOG during the first 4 weeks of treatment and continued to grow until the end of the 7 weeks of treatment (p=0.036). The relative D1DR gene expression in the cerebral cortex was significantly higher compared to the relative expression mRNA in the hippocampus region (D1DR 1.6 fold, p